The teamnotebook. Axis of the cooperative learning methodology in a Secondary Education master's subject. - Guillermo Domínguez Fernández; José Rafael Prieto García; Francisco Javier Álvarez Bonilla (Universitat Politècnica de València, 2012)
The "Department of Guidance and mentoring in Secondary Education" subject is included in the Master's Degree in Education at the Pablo de Olavide University (Seville). This subject meant the collaboration of different departments and disciplines of the Social Science's Faculty. Team Notebook has been the main methodological tool for cooperative learning and the way of assessing their learning experience. The results focus on concepts learning, especially the procedural and emotional components of teaching-learning process.